The spy who dumped me [videorecording (DVD)] - Fogel, Susanna; Kunis, Mila, 1983-; McKinnon, Kate, 1984-; Theroux, Justin; Heughan, Sam, 1980-; Anderson, Gillian, 1968-; Curtin, Jane (Lions Gate Entertainment, 2018)
Audrey and Morgan are two fairly ordinary 30-year-old women who live in Los Angeles. They are best friends, and they always stick together, so when Audrey discovers her ex-boyfriend is an international spy, Morgan joins her on an unlikely adventure. Together, the two of them must try to save him from assassins and help to save the world from a dangerous threat. As they travel around the globe with killers hot on their heels, they will discover hidden reserves of strength and cleverness that neither one of them knew they had.